Cu/Zn superoxide dismutase enzyme immunoreactivity in the stomach tissue of rats fed with mussels (Mytilus galloprovincialis) - Muratlı, Aslı; Gezen, Mehmet Rıza (The European Research Journal, 2019)
Objectives: Mussels accumulate heavy metals in their tissues. Although there are few data about the toxicity of seafood that is exposed to environmental pollution, there are no animal studies about the gastric toxicity of mussels grown in the Dardanelles. The antioxidant Cu/Zn superoxide dismutase (Cu/Zn SOD) enzyme catalyzes the hydrogen peroxide dismutation of superoxide radicals and removes the effects of free radicals which cause oxidative stress. The purpose of the study was to demonstrate the Cu/Zn SOD in the stomach tissues of rats which are fed with mussels that are collected from the Çamburnu region of the Dardanelles.Methods: A total of 24 male Wistar albino rats were randomly divided into four groups: Group 1 (n = 6), control group fed with standard rat food; Group 2 (n = 6), 75% mussels and 25% standard rat food daily; Group 3 (n = 6), 75% mussels and 25% standard rat food every two days; and Group 4 (n = 6), 75% mussels and 25% standard rat food every three days. To detect Cu/Zn SOD localization in the tissues, the LAB-SA Detection System was used.Results: Cu/Zn SOD enzyme immunoreactivity was not detected in Group 1 and in samples without Cu/Zn SOD primer antibody. Cu/Zn SOD enzyme immunoreactivity was detected 82% in Group 2, 79% in Group 3, and 61% in Group 4. There was statistically significant difference between the Cu/Zn SOD immunoreactivity of epithelial cells in the gastric mucosa of the rats in the experimental and control groups (p < 0.05).Conclusions: Determination of the increase of Cu/Zn SOD enzyme in the gastric mucosa of mussel-fed rats that we used in our study suggests that it triggers the antioxidant defense mechanism against mussel toxicity.